Achieving Door-to-Balloon Times That Meet Quality Guidelines - Bradley, Elizabeth H.; Roumanis, Sarah A.; Radford, Martha J.; Webster, Tashonna R.; McNamara, Robert L.; Mattera, Jennifer A.; Barton, Barbara A.; Berg, David N.; Portnay, Edward L.; Moscovitz, Harry; Parkosewich, Janet; Holmboe, Eric S.; et al. (Journal of the American College of Cardiology, 2005)
We sought to recommend an approach for minimizing preventable delays in door-to-balloon time on the basis of experiences in top-performing hospitals nationally. Prompt percutaneous coronary intervention (PCI) for patients with ST-segment elevation myocardial infarction (STEMI) significantly reduces mortality and morbidity; however, door-to-balloon times often exceed the 90-min guideline set forth by the American College of Cardiology (ACC) and the American Heart Association (AHA). We conducted a qualitative study using in-depth interviews (n = 122) of hospital staff at hospitals (n = 11) selected as top performers based on data from the National Registry of Myocardial Infarction from January 2001 to December 2002. We used the constant comparative method of qualitative data analysis to synthesize best practices across the hospitals. Top performers were those with median door-to-balloon times of ≤90 min for their most recent 50 PCI cases through December 2002 and the greatest improvement in median door-to-balloon times during the preceding four-year period 1999 to 2002. Several critical innovations are described, including use of pre-hospital electrocardiograms (ECGs) to activate the catheterization laboratory, allowing emergency physicians to activate the catheterization laboratory, and substantial interdisciplinary collaboration throughout the process. In the ideal approach, door-to-balloon time is 60 min for patients transported by paramedics with a pre-hospital ECG and 80 min for patients who arrive without paramedic transport and a pre-hospital ECG. Hospitals can achieve the recommended ACC/AHA guidelines for door-to-balloon time with specific process design efforts. However, the recommended best practices involve extensive interdisciplinary collaboration and will likely require explicit strategies for overcoming barriers to organizational change.